Manajemen Pendidikan Agama Kristen dalam Ketahanan Keluarga - Dandi Joel Polii; Meyva Polii (EDULEAD: Journal of Christian Education and Leadership, 2022)
Family resilience in over the last years has received special attention because the high divorce rate in Indonesia to increasing. Many families are unable to maintain family resilience because of various background problems, namely; starting from economic problems, disputes, and third person game in the family. In this case, the Christian family is no exception. This can be seen the data that has been obtained from various research results first. This paper aims to explain how the management of Christian Religious Education on family can maintain family resilience by applying management principles so that families are able to maintain harmonious relationship, children have good spiritual qualities, families become the main protectors through rules and supervision and the establishment of effective communicationthe goals. This research uses description method and literature review. This means that this research will use various literature references that are directly related to describing the benefits of Christian Religious Education management in maintaining family resilience.AbstrakKetahanan keluarga di tahun-tahun belakangan ini mendapat perhatian khusus oleh karena angka perceraian yang ada di Indonesia terus mengalami peningkatan. Banyak keluarga yang tidak dapat menjaga ketahanan keluarga oleh karena berbagai latar belakang masalah yakni; mulai dari masalah ekonomi, perselisihan, sampai pada adanya orang ketiga di dalam keluarga. Dalam hal ini, keluarga Kristen pun tidak terkecuali. Hal ini bisa dilihat data yang telah ada dari berbagai hasil penelitian terlebih dahulu. Tulisan ini bertujuan untuk memaparkan bagaimana manajemen PAK keluarga dalam dapat menjaga ketahanan keluarga dengan menerapkan prinsip-prinsip manajemen sehingga keluarga mampu menjga hubungan yang harmonis, anak-anak memiliki kualitas rohani yang baik, keluarga menjadi pelindung utama melalui aturan dan pengawasan dan terjalinnya komunikasi yang efektif. Penelitian ini menggunakan metode deskripsi dan kajian literatur. Artinya penelitian ini akan menggunakan berbagai referensi literatur yang bersinggung langsung dengan mendeskripsikan manfaat manajemen PAK dalam menjaga ketahanan keluarga.